Pattern of Pediatric Morbidity in Hospital Admitted Patients in Western Region of Nepal - Adhikari, P; Kandel, D; Shrestha, U (Journal of Gandaki Medical College-Nepal, 2018)
Background: Pediatric age group comprises the important fraction of hospital admissions in our health care settings and it is the major challenge to address in the developing countries like ours. This study was carried out to find out the significant epidemiological trends and disease patterns of the admitted children in a pediatric ward.Methods: This retrospective study was carried out by reviewing hospital records of the patients admitted in the pediatric ward from July 2015 to January 2016 in Gandaki Medical College Teaching Hospital. The disease pattern was analyzed on the basis of age, sex, final diagnosis of the disease, duration of hospital stay and months of admission.Results: Among the 1348 admitted children during the study period, majority were males (65%) and below five years (74%). Lower respiratory tract infections (30%), enteric fever (10%) and acute gastroenteritis (7.7%) were the three major causes for admission. The mean days of hospital stay was 4.43 and maximum number of children was admitted during August/September.Conclusion: Infectious diseases are the major cause for morbidity and more were during the rainy season.J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 61-63